2019
DOI: 10.1039/c8mh01013g
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the structure and magnetic properties of cluster-assembled metallic glasses

Abstract: The local structure and magnetic properties of amorphous materials are controlled by the impact energy of amorphous clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…A different approach considers the fabrication of materials characterized by nanocrystalline grains of various dimensions with a precise control of the degree of interaction of the nanoscale components, or, in other terms, of their degree of compaction [5,11] (Figure 1(b)). In this case, a precise mass selection of the nanoscale building blocks is not required, thus allowing the production in bulk quantities.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach considers the fabrication of materials characterized by nanocrystalline grains of various dimensions with a precise control of the degree of interaction of the nanoscale components, or, in other terms, of their degree of compaction [5,11] (Figure 1(b)). In this case, a precise mass selection of the nanoscale building blocks is not required, thus allowing the production in bulk quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel metallic glasses that exhibit distinct structural features have been developed, which are the so-called nanoglasses. As schematically shown in Figure a, a nanoglass consists of amorphous nanometer-sized grains connected by amorphous interfaces (glass–glass interfaces). Arguably, nanoglass provides a testing benchmark for the possible correlation between structure and dynamics in the glass system.…”
mentioning
confidence: 99%
“…The glassy nanoparticles are produced by the inert gas condensation technique using helium gas as a quencher medium. However, other methods are also used to produce the nanostructured glassy materials, including electrolysis, sputtering, and molecular beam epitaxy (Ivanisenko et al, 2018;Mohri et al, 2018;Benel et al, 2019;Singh et al, 2020a;Chen et al, 2020).…”
Section: Spd In Nanostructured Metallic Glassmentioning
confidence: 99%
“…However, recently, with the availability of advanced characterization techniques and simulation tools, it has been found that there is chemical inhomogeneity at the atomic level in the MG. Moreover, in recent times, there have been reports on the synthesis of nanostructured MG termed as nanoglass using techniques such as inert gas condensation, sputtering, and electrolysis (Stoesser et al, 2014;Sniadecki et al, 2016;Guo et al, 2017;Mohri et al, 2018;Benel et al, 2019;Chen et al, 2019). These nanoglasses have demonstrated exciting properties that have not been seen in the bulk MG of the same chemical compositions.…”
Section: Introductionmentioning
confidence: 99%